2010
DOI: 10.1021/jf103068w
|View full text |Cite
|
Sign up to set email alerts
|

GMI, a Ganoderma Immunomodulatory Protein, Down-regulates Tumor Necrosis Factor α-Induced Expression of Matrix Metalloproteinase 9 via NF-κB Pathway in Human Alveolar Epithelial A549 Cells

Abstract: Matrix metalloproteinase 9 (MMP-9) has been implicated in airway injury in chronic obstructive pulmonary disease (COPD), lung inflammation, and lung cancer and plays a major role in tumor necrosis factor-α (TNF-α)-stimulated tumor invasion and lung inflammation. MMP-9 activity is promoted by the pro-inflammatory cytokine TNF-α. GMI, cloned from Ganoderma microsporum and purified, is one of the recombinant fungal immunomodulatory proteins. To understand the molecular mechanisms involved in the suppression of TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 28 publications
(31 reference statements)
1
37
0
Order By: Relevance
“…Previous studies demonstrated that rLZ-8 and rFIP-gts inhibited cell proliferation by increasing G1 arrest [33,34,35,36], rFIP-fve suppressed A549 cell proliferation via the p53 activation pathway [37] and FIP-gmi inhibited metastatic ability regulated by epidermal growth factor in A549 cells [38]. These observations suggest that FIPs can be therapeutic.…”
Section: Resultsmentioning
confidence: 84%
“…Previous studies demonstrated that rLZ-8 and rFIP-gts inhibited cell proliferation by increasing G1 arrest [33,34,35,36], rFIP-fve suppressed A549 cell proliferation via the p53 activation pathway [37] and FIP-gmi inhibited metastatic ability regulated by epidermal growth factor in A549 cells [38]. These observations suggest that FIPs can be therapeutic.…”
Section: Resultsmentioning
confidence: 84%
“…Specific binding was confirmed with a 200-fold excess of unlabeled probe as a specific competitor. Gel shifts were visualized with a streptavidin-HRP followed by chemiluminescent detection (Lin et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…After incubation with berberine, cells were collected and disrupted by the Luciferase Assay System (Promega, San Diego, CA). Firefly luciferase activities were standardized for b-galactosidase activity (Lin et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The examples include Fip-vvo from Volvariella volvacea [43], GMI from Ganoderma microsporum [44, 45], IPAF from Anoectochilus formosanus [46], AAL and AAL-2 from Agrocybe aegerita [47, 48], and immunomodulatory protein LZ-8 from G . lucidum [49, 50].…”
Section: Introductionmentioning
confidence: 99%